PERSEPSI GURU BK SEKOLAH MITRA TERHADAP PELAKSANAAN PROGRAM PENGAJARAN DI SEKOLAH (PPS) MAHASISWA PROGRAM STUDI BIMBINGAN DAN KONSELING FKIP ULM DI SMP SE-KOTA BANJARMASIN - Ririanti Rachmayanie Jamain; Muhammad Andri Setiawan; Noor Anida Rahmida (Program Studi Bimbingan dan Konseling, Universitas Pattimura, 2019)
This study aims to describe the perceptions of school partner guidance teachers on students from the Lambung Mangkurat University guidance and counseling study program who take teaching practices in schools based on the four competencies of the Permendiknas Number 27 of 2008 concerning standard academic qualifications and counselor competencies.. The research method used was simple descriptive with the formulation of a simple percentage analysis with 39 respondents from 14 partner schools. The results of the study place the professional competence of professional competencies as competencies that are considered the highest (64.6%) and the other three competencies are in the position of good category. Therefore, it is recommended that the Guidance and Counseling Study Program administrators together with school partner guidance teachers be able to improve the education process, because the results of this study actually show an overview of the educational process of guidance and counseling.